SSC (English Medium) Class 8Maharashtra State Board
Share

# Solve the Following Equations. - SSC (English Medium) Class 8 - Mathematics

ConceptSolution of Equations in One Variable

#### Question

Solve the following equation.

("x" - 9)/("x" - 5) = 5/7

#### Solution

("x" - 9)/("x" - 5) = 5/7

Multiplying both sides by 7

⇒ 7 (("x" - 9)/("x" - 5)) = 5/7 xx 7

⇒ (7"x" - 63)/("x" - 5) = 5

Multiplying both sides by (x - 5)

⇒ (7"x" - 63)/("x" - 5) (x - 5) = 5(x - 5)

⇒ 7x - 63 = 5x -25

⇒ 7x - 63 + 63 = 5x - 25 + 63

⇒ 7x - 63 = 5x - 38

Subtracting 5x from both sides

⇒ 7x - 5x = 5x + 38 - 5x

⇒ 2x = 38

Dividing both sides by 2

⇒ (2"x")/2 = 38/2

⇒ x = 19

Hence, x = 19 is the solution of the equation.

Is there an error in this question or solution?

#### APPEARS IN

Balbharati Solution for Balbharati Class 8 Mathematics (2019 to Current)
Chapter 12: Equations in one variable
Practice Set 12.1 | Q: 2.09 | Page no. 77
Solution Solve the Following Equations. Concept: Solution of Equations in One Variable.
S